Characteristics and source analysis of polycyclic aromatic hydrocarbons in organisms and manure near Ardley Island, Antarctica. (March 2023) - Han, Bin; Wang, Gui; Liu, Ang; Zheng, Yunchao; Zheng, Li; Ding, Runtian
Abstract: In order to better understand the migration and accumulation behavior of polycyclic aromatic hydrocarbons (PAHs) in biological chains in the cold environment around the Ardley Island, a variety of biological and penguin manure samples during China's 36th Antarctic Scientific expedition have been collected and studied. A certain difference in PAHs concentration was observed in the environmental samples, and the order of size was as follows: fish > limpets > krill > manure > brown alga > mosses. The percentage of PAHs with different ring numbers in brown alga, moss, and krill was in the following order: three rings > two rings > four rings > five rings > six rings. The proportion of HMW-PAHs in limpets and fish samples was higher than that in brown alga, moss, manure, and krill samples. The main source of PAHs in environmental samples near Ardley Island is oil, which may be due to the development of tourism in Antarctica, the number of ships and human activities around the region. Therefore, it is imperative to strengthen the protection of the ecological environment in the area around Ardley Island. Highlights: Distribution of PAHs in organisms and manure near Ardley Island, Antarctica Traceability of PAHs by characteristic ratios Recommendations for the protection of the surroundings of the Ardley Island